Metode Simple Additive Weighting Dalam Pengukuran Prestasi Karyawan - Fahrullah, Fahrullah; Muhammad Syahnur; Yepa Bintan (Kodepena (Komunitas Dosen Penulis dan Peneliti Indonesia), 2024)
Employees in an organization or company are an important asset in addition to other resources. Having employees who are highly dedicated will certainly greatly affect the continuity and progress of the company, especially in the face of global competition, of course, employees who are ready to face it are needed. PT. Nagabhuana Group Unit 7 Samarinda, which is a growing company, has prepared all of this, one of which is by boosting employee motivation by giving awards to employees with the best performance in the form of bonuses, incentives and certificates of appreciation. To be able to make an objective and more accurate assessment, of course, a decision support system is needed that can help overcome these problems. By using the Simple Additive Weighting Method (SAW) the HRD manager of PT. Nagabhuana can be helped in determining the best employees in his company, the results obtained from the calculation of the Simple Additive Weighting Method are very fast and precise so that it can minimize errors that can certainly harm employees